An overview of orthodontic material degradation in oral cavity - Chaturvedi T; Upadhayay S (Wolters Kluwer Medknow Publications, 2010)
Various types of metallic orthodontic appliances are used in the management of malocclusion. These appliances are placed in oral environnent under many stresses and variations such as masticatory forces, appliance loading, temperature fluctuations, varieties of ingested food and saliva. These metals undergo electrochemical reactions with the oral environment resulting in dissolution or formation of chemical compounds. Various microorganisms and many aggressive ions containing oral environment can cause material degradation (corrosion) and its associated problems during long time exposure. Orthodontic alloys must have excellent corrosion resistance to the oral environment, which is highly important for biocompatibility as well as for orthodontic appliance durability. This article reviews various aspects of corrosion (surface degradation) of orthodontic alloys. It explores the emerging research strategies for probing the biocompatibility of materials. During orthodontic treatment, use of nickel free, better corrosion resistance alloys and less use of fluoride containing toothpaste or gel is expected.